TwinXR: Method for using digital twin descriptions in industrial eXtended reality applications - Tu, Xinyi; Autiosalo, Juuso; Ala-Laurinaho, Riku; Yang, Chao; Salminen, Pauli; Tammi, Kari (Frontiers in Virtual Reality, 2023)
Digital twins (DTs) and eXtended Reality (XR) are two core technological enablers for engineering in the Metaverse that can accelerate the human-centric Industry 5.0 transformation. The DT technology provides a digital representation of a physical asset with data linkages for inspection, monitoring, and prediction of complex processes or systems, while XR offers real-and-virtual combined environments for human users to interact with machines. However, the synergies between DTs and XR remain understudied. This work addresses this research gap by introducing a novel method “TwinXR” that leverages ontology-based descriptions of DTs, i.e. DT documents, in industrial XR applications. To ease the use of the TwinXR method, we publish a Unity package that allows data flow and conversion between XR applications and DT documents on the server. Finally, the work applies the TwinXR method in two industrial XR applications involving overhead cranes and a robot arm to demonstrate the use and indicate the validity of the method. We conclude that the TwinXR method is a promising way to advance the synergies between DTs and XR: For XR, TwinXR enables efficient and scalable XR development; For DTs, TwinXR unlocks and demonstrates the potential of DTs for data interchange and system interoperation. Future work includes introducing more detailed principles of Semantic Web and Knowledge Graph, as well as developing factory-level TwinXR-compatible applications.